Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1534/genetics.116.194811
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ectopic Gene Conversion in the Evolution of a Candida krusei Pleiotropic Drug Resistance Transporter Family

Abstract: Gene duplications enable the evolution of novel gene function, but strong positive selection is required to preserve advantageous mutations in a population. This is because frequent ectopic gene conversions (EGCs) between highly similar, tandem-duplicated, sequences, can rapidly remove fate-determining mutations by replacing them with the neighboring parent gene sequences. Unfortunately, the high sequence similarities between tandem-duplicated genes severely hamper empirical studies of this important evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 84 publications
2
15
0
Order By: Relevance
“…The role of gene conversion is supported by two key pieces of evidence: 1) unique amino acid tracts that are shared by KAP1 copies within a species, but are unique to that species/group of related species; and 2) the possession of shared nucleotide variants between KRTAP1 gene copies in sheep populations. These results extend previous reports of homogenization via ongoing short-tract gene conversion events in other protein coding genes (Noonan, et al 2004; Lamping, et al 2017).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The role of gene conversion is supported by two key pieces of evidence: 1) unique amino acid tracts that are shared by KAP1 copies within a species, but are unique to that species/group of related species; and 2) the possession of shared nucleotide variants between KRTAP1 gene copies in sheep populations. These results extend previous reports of homogenization via ongoing short-tract gene conversion events in other protein coding genes (Noonan, et al 2004; Lamping, et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Repeats are ubiquitous denizens of eukaryote genomes, where they exist in different forms (coding, non-coding) and organizations (tandem, dispersed). Our results add to the growing list of examples that illustrate how different molecular and evolutionary processes can impinge on repeats to structure their sequences and create distinctive patterns of evolution (Shyue, et al 1994; Noonan, et al 2004; Ganley and Kobayashi 2007; Storz, et al 2007; Hiwatashi, et al 2011; Lamping, et al 2017). However, it is unclear how widespread these sorts of evolutionary dynamics are for eukaryotic gene repeats, largely because the patterns of evolution have not been investigated for the vast majority of multi-gene families.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…There is also uncertainty about the ploidy of the species. The MLST study indicated that isolates are diploid [ 24 ], as did two genome analyses [ 10 , 23 ], but evidence of triploid and aneuploid strains has also been reported [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fluconazole resistance in C . krusei is not fully understood but appears to have two causes: its ergosterol synthesis enzyme Erg11 has unusually low affinity for fluconazole, and the drug efflux pumps Abc1 and Abc11 are constitutively expressed [ 26 , 27 ]. Echinocandins such as micafungin are the current drugs of choice for treatment of C .…”
Section: Introductionmentioning
confidence: 99%